2021
DOI: 10.3390/ijerph18052578
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and SARS-CoV-2 Infection in the First Pandemic Wave in Spain

Abstract: After the first pandemic wave, a nationwide survey assessed the seroprevalence of SARS-CoV-2 antibodies in Spain and found notable differences among provinces whose causes remained unclear. This ecological study aimed to analyze the association between environmental and demographic factors and SARS-CoV-2 infection by province. The seroprevalence of SARS-CoV-2 antibodies by province was obtained from a nationwide representative survey performed in June 2020, after the first pandemic wave in Spain. Linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…On the basis of the geographical regions of Africa, the meta-analysis results indicated that Central and Western Africa had higher seroprevalence rates (26.5% and 22.0%, respectively) than Southern (20.7%), Eastern (12.1%) and Northern (6.5%) Africa. Considering the limited evidence regarding the influence of environmental and demographic factors on SARS-CoV-2 transmission [ 79 ], neither the high seropositivity in Central Africa nor the low seropositivity in Northern Africa could accurately reflect the real status in these regions due to the few number of eligible studies in some regions. For instance, only one nation from Southern Africa and two from Northern Africa were included.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the geographical regions of Africa, the meta-analysis results indicated that Central and Western Africa had higher seroprevalence rates (26.5% and 22.0%, respectively) than Southern (20.7%), Eastern (12.1%) and Northern (6.5%) Africa. Considering the limited evidence regarding the influence of environmental and demographic factors on SARS-CoV-2 transmission [ 79 ], neither the high seropositivity in Central Africa nor the low seropositivity in Northern Africa could accurately reflect the real status in these regions due to the few number of eligible studies in some regions. For instance, only one nation from Southern Africa and two from Northern Africa were included.…”
Section: Discussionmentioning
confidence: 99%
“…Several months after the COVID-19 pandemic declaration on 11 March 2020, some interrogations still remain unsolved concerning viral transmission and the burden of COVID-19 at high-altitude locations [1][2][3]. The variability and susceptibility of COVID-19 infection throughout the world have been attributed to several factors such as chronic diseases, age, socioeconomic level, and access to medical care within different health care systems, among others [4]; however, the role of different environmental factors such as humidity, temperature, or altitude on the transmission of SARS-CoV-2 are not wellunderstood [4,5]. Since the onset of the pandemic, some researchers have attempted to elucidate the effects of living at a high altitude on the spread of the SARS-CoV-2 virus or on the severity and the COVID-19-related incidence and mortality rate [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…En la primera onda pandémica de COVID-19 hemos estimado que contrajo la infección alrededor del 10,3 % de la población de Navarra, aunque solo en el 1,6 % se llegó a confirmar el diagnóstico, y al final de la onda pandémica el 7 % mantenía un nivel de anticuerpos detectable. La prevalencia alcanzada tras la primera onda pandémica indica un nivel de infección en Navarra por encima de la media de España 7 , con diferencias geográficas que podrían explicarse en buena parte por factores medioambientales y climáticos que sitúan a Navarra entre las provincias con condiciones desfavorables para el control de la transmisión 16 .…”
Section: Discussionunclassified